The Role of Small and Medium Enterprises in Job Creation: A Case Study of Karachi, Hyderabad and Sukkur (Journal of Asian Development Studies, 2025)
Small and Medium Enterprises (SMEs) play a vital role in Pakistan’s economic development, particularly in job creation and poverty alleviation. This research paper examines the impact of SMEs on employment generation in three major cities of Sindh province: Karachi, Hyderabad, and Sukkur. Utilizing both quantitative and qualitative methodologies including surveys and interviews with SME owners, employees, and government officials the study offers a comprehensive analysis of the contribution of SMEs to local economies. The research findings given in this Paper reveal that the   Small and medium enterprise played a due role to reduce poverty in the country through SMEs because in every SMEs 110-15 people were working for their livelihood. The analysis also demonstrated that through SMEs employment dramatically improved in the study region. The people income, saving and expenditure increased significantly, due to this reason expend more for their health. The findings reveal that while SMEs significantly contribute to employment, they also face numerous challenges such as limited access to finance, regulatory constraints, and inadequate infrastructure. Despite these obstacles, SMEs demonstrate considerable resilience and possess strong potential for future growth.